Obstáculos Epistemológicos de Bachelard: análise do tema água em livros didáticos de Ciências do sexto ano do ensino fundamental - Santos, Natiely Quevedo dos (2019)
The present work includes the analysis in textbooks of Sciences, referring to the content water worked in the discipline of Sciences in the sixth year of elementary school. The objective was to analyze how the theme water is presented in Science textbooks that were approved by PNLD / 2017 and if there is the presence of Epistemological Obstacles in the way this content is approached, identifying and analyzing some of them. For this purpose, we performed a qualitative evaluation using the analysis of the content present in the books based on the notion of Epistemological Obstacles proposed by Bachelard (1996). For this author Epistemological Obstacles may constitute a resistance to the construction of scientific knowledge. Studies related to Epistemological Obstacles such as those proposed by Gaston Bachelard should be considered as a way to allow advances in the formation of students and teachers alerting to the greater concern with the teaching-learning process, allowing reflections on this. Before the analysis in the books, we show the presence of Epistemological Obstacles, among them, all the books analyzed are: 1) the obstacle of quantitative knowledge, having as possible cause, the need to quantify the water before its availability, use and presence in living organisms; 2) the substantialist obstacle in eleven of the thirteen books analyzed, due to the attribution of qualities to the water in which they often appear to be exclusive to it; 3) the obstacles of general knowledge, verbal, first, unitary and pragmatic, realistic and animistic, being a possible cause attributed to the attempt to simplify scientific or abstract terms to facilitate the construction of knowledge on the subject. From the analysis developed, it was possible to note the need to recognize and overcome Epistemological Obstacles present in textbooks since these are the resources most used in the classroom and that aim to promote the learning of the student, thus making it necessary to alert to a greater preoccupation with the insertion of scientific language in the daily school life, mainly to emphasize the importance of the reflection of the teaching practice and of the organization and systematization with the use of analogies and metaphors